Developing the manufacturer pharmacopoeia article of the wound treatment gel “The Fomitop” - Narmandakh, Shinen; Davaadulam, Byamba; Khulan, Gansukh; Sumyabazar, Erdenechimeg; Li, Yshen (Bulletin of the Institute of Chemistry and Chemical Technology, 2022)
Fomitopsis officinalis (Vill. ex Fr. Bond. et Sing) (agarikon fungus) is a medicinal fungus that contains many pharmacologically active compounds. In folk medicine, the agarikon fungus is traditionally used to treat asthma, tuberculosis, liver disease and gynecological diseases. In our previous research, we extracted a dry extract from agarikon fungus, prepared "Fomitop" gel with its ingredients, and studied its antibiotic properties. Research has shown that it inhibits the growth of bacteria such as Staphylococcus aureus, Micrococcus luteus, Bacillus subtilis, and Enterococcus faecalis, and accelerates the regeneration of aseptic and burn wounds caused in experimental animals and has a short-term healing effect. "Fomitop" gel has bactericidal and wound healing properties, this research was carried out in order to determine the content of biologically active substances, to determine the standard parameters for checking its quality when used as pharmaceutical preparations, and then to develop a draft article for the manufacturer's pharmacopoeia. Within the scope of the study, the content of organic acids, total phenolic compounds, and triterpene compounds, the main active substances of gel, was determined using the methods of the National Pharmacopoeia of Mongolia and Russia. As a result of the study, it was determined that the content of organic acids in gel is 0.34%, the content of total phenolic compounds is 2.3% when transferred to gallic acid, and the content of triterpene compounds is 1.53% when transferred to oleanolic acid. As a result of the research, the content of biologically active substances of "Fomitop" gel prepared from the dry extract of agarikon fungus was determined, the permissible limits of standardization were set, and a draft of the "Fomitop gel" was developed. Шарх эмчлэх үйлдэлтэй “Фомитоп” гелин түрхлэгийн үйлдвэрлэгчийн фармакопейн өгүүлэл боловсруулах нь Хураангуй: Монгол оронд ургадаг эмийн ач холбогдолтой мөөгний нэг бол хар модны агил мөөг Fomitopsis officinalis ((Vill.) Bond.et Singer) юм. Бид өмнө хийсэн судалгааны дүнд агил мөөгний хуурай ханд агуулсан “Фомитоп” гелин түрхлэг нь бактер устгах, шарх эмчлэх үйлдэлтэй байгааг тогтоосон бөгөөд энэхүү биологийн идэвхтэй “Фомитоп” гелин түрхлэгийн биологийн идэвхт бодисын агууламжийг тодорхойлох, эмийн бэлдмэлээр ашиглах үед түүний чанарыг шалгах, стандарт үзүүлэлтийг тогтоох үйлдвэрлэгчийн фармакопейн өгүүллийн төсөл боловсруулах зорилгоор энэхүү судалгааг гүйцэтгэв. Судалгааны хүрээнд гелин түрхлэгийн үндсэн үйлчлэгч бодис болох органик хүчил, нийлбэр фенолт нэгдэл, тритерпений нэгдэл зэргийн агууламжийг тогтоосон. Ингэхдээ Монгол улсын болон Орос улсын Үндэсний фармакопейн арга аргачлалыг ашигласан. Судалгааны үр дүнд гелин түрхлэгт ерөнхий органик хүчлийн агууламж 0.34%, нийлбэр фенолт нэгдлийн агууламж галлийн хүчилд шилжүүлснээр 2.3%, тритерпений нэгдлийн агууламж олеаноловын хүчилд шилжүүлснээр 1.53% болохыг тус тус тогтоов. Ийнхүү судалгааны үр дүнд агил мөөгний хуурай хандтай “Фомитоп” гелин түрхлэгийн биологийн идэвхт бодисын агууламж болон стандартчиллын зөвшөөрөгдөх хязгаарыг тогтоож, “Фомитоп гелин түрхлэг” нэртэй ҮФӨ-ийн төслийг боловсруулав. Түлхүүр үг: фармакопейн шаардлага, тритерпений нэгдэл, нийлбэр фенолт нэгдэл, органик хүчил